Disrupted mitochondrial network drives deficits of learning and memory in a mouse model of FOXP1 haploinsufficiency - Wang, Jing; Rappold, Gudrun; Fröhlich, Henning (Genes, 2022)
Reduced cognitive flexibility, characterized by restricted interests and repetitive behavior, is associated with atypical memory performance in autism spectrum disorder (ASD), suggesting hippocampal dysfunction. FOXP1 syndrome is a neurodevelopmental disorder characterized by ASD, language deficits, global developmental delay, and mild to moderate intellectual disability. Strongly reduced Foxp1 expression has been detected in the hippocampus of Foxp1+/− mice, a brain region required for learning and memory. To investigate learning and memory performance in these animals, fear conditioning tests were carried out, which showed impaired associative learning compared with wild type (WT) animals. To shed light on the underlying mechanism, we analyzed various components of the mitochondrial network in the hippocampus. Several proteins regulating mitochondrial biogenesis (e.g., Foxo1, Pgc-1α, Tfam) and dynamics (Mfn1, Opa1, Drp1 and Fis1) were significantly dysregulated, which may explain the increased mitophagy observed in the Foxp1+/− hippocampus. The reduced activity of complex I and decreased expression of Sod2 most likely increase the production of reactive oxygen species and the expression of the pre-apoptotic proteins Bcl-2 and Bax in this tissue. In conclusion, we provide evidence that a disrupted mitochondrial network and the resulting oxidative stress in the hippocampus contribute to the altered learning and cognitive impairment in Foxp1+/− mice, suggesting that similar alterations also play a major role in patients with FOXP1 syndrome.